Epigenetic Signaling of Cancer Stem Cells During Inflammation - Liu, Zaoqu; Ren, Yuqing; Meng, Lingfang; Li, Lifeng; Beatson, Richard; Deng, Jinhai; Zhang, Tengfei; Liu, Junqi; Han, Xinwei (Frontiers in Cell and Developmental Biology, 2021)
Malignant tumor has been a big conundrum for human beings, there has been increasingly more tumor pathogenesis has been elucidated. Cancer stem cells are considered to have a profound impact on tumorigenesis and development, and are also a critical cause of drug resistance. Among them, the study of the relationship between inflammation and cancer stem cells has received much attention in recent years, but its mechanism has not been fully elucidated. Inflammatory cytokines produced in chronic inflammation activate signaling pathways that regulate the generation of CSCs, which involve epigenetic alterations. In this review, we have focused on the effects of inflammation on cancer stem cells, especially the role of signaling pathways involving epigenetic changes, such as NF-κB pathway, STAT3 pathway and Smad pathway, hoping to provide a new perspective for improving tumor treatment modalities.